The Effect of YouTube Nihongo Mantappu Exposure toward Dharma Wanita 8 Waru Middle School Students’ Interest in Learning Mathematics: (Study on The Content of Battle Matematika) - Jihan Rifdah Yumna; Anam Miftakhul Huda (Metafora: Education, Social Sciences and Humanities Journal, 2022)
This study looks at the effect of YouTube Nihongo Mantappu exposure toward Dharma Wanita 8 Waru Middle School students' interest in learning mathematics. The applied method was an experimental method with a questionnaire used as a research instrument. The type of experiment used is The One Group Pretest-Posttest Design. This study used all 7th, 8th, and 9th-grade students of Dharma Wanita 8 Waru Middle School as the population. The sample in this study amounted to 54 students of Dharma Wanita 8 Waru Middle School, which were determined through the total sampling technique because the population was less than 100 people. The data analysis method used is the Paired Sample T-Test, tested using SPSS Statistics 26. The hypothesis formulated in this study is accepted. This study showed an increase in Dharma Wanita 8 Waru Middle School students' interest in learning mathematics after receiving YouTube Nihongo Mantappu exposure.